IMPUNITY AND INTERNATIONAL LAW - Mattarollo, Rodolfo (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 1998)
The laws of punto final and due obedience violate international law as it stands today. Indeed, such laws breach the right to legal recourse and perpetrate impunity. The United Nations is presently drafting a set of principles to struggle against impunity. This “progressive development” of international law is in reaction to a wave of new atrocities in the last decade. Another, and most recent manifestation of this “progressive development”: in July 1998, a diplomatic conference was held in Rome and has created an International Criminal Court. This initiative, together with the ad hoc tribunals for the former Yugoslavia and for Rwanda, has breathed new life into the efforts to combat impunity, and suggests that there is a growing consensus within the international community regarding responsibility for crimes against humanity and gross human rights violations. One important consequence of this evolution is the obligation of all States to bring their domestic law into line with international law. In this respect, they must incorporate into their criminal legislation, crimes such as crimes against humanity, genocide, summary executions, torture and enforced disappearances. States should also remove and nullify, Argentina in this case as exposed by the author, any domestic legislation that interfere with international law in this field.